2022
DOI: 10.48550/arxiv.2207.11772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perturbative unitarity and NEC violation in genesis cosmology

Abstract: Explorations of the violation of null energy condition (NEC) in cosmology could enrich our understanding of the very early universe and the related gravity theories. Although a fully stable NEC violation can be realized in the "beyond Horndeski" theory, it remains an open question whether a violation of the NEC is allowed by some fundamental properties of UV-complete theories or the consistency requirements of effective field theory (EFT). We investigate the tree-level perturbative unitarity for stable NEC vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Nevertheless, scenarios that involve NEC violation have been conjectured to account for a range of early Universe phenomena, including the inflationary epoch and the genesis of primordial black holes [25][26][27][28][29][30][31][32]; see, for example, the review by [21]. Advances in modified gravity theories, especially within the framework of "beyond Horndeski" models [33][34][35][36][37][38][39], have shown that stable NEC violations are theoretically feasible, circumventing the issue of pathological instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, scenarios that involve NEC violation have been conjectured to account for a range of early Universe phenomena, including the inflationary epoch and the genesis of primordial black holes [25][26][27][28][29][30][31][32]; see, for example, the review by [21]. Advances in modified gravity theories, especially within the framework of "beyond Horndeski" models [33][34][35][36][37][38][39], have shown that stable NEC violations are theoretically feasible, circumventing the issue of pathological instabilities.…”
Section: Introductionmentioning
confidence: 99%